Social Practices of Marginal Class Characters in Brian Khrisna's Novel Sisi Tergelap Surga According to Bourdieu's Perspective - Nova Rahma Dinna; Anas Ahmadi (Raja Zulkarnain Education Foundation, 2026)
The novel